Considerações metodológicas e características socioeconômicas em uma população de near miss neonatal em uma maternidade de risco habitual - Cruz, Nicolas Magno Santos (2018)
In most parts of the world there is a gradual reduction in the infant mortality rate. Many factors are considered as reponsible, such as medical care, income increase, schooling, sanitary conditions, immunization programs. Brazil has achieved the goal set by the UN to reduce child mortality by two-thirds. Neonatal deaths represent a very significant part of the composition of infant mortality. Within the neonatal deaths, a population of newborns presents particular fragility, are the near miss. The concept of neonatal near miss has been shown to be a useful tool to evaluate the quality of neonatal health care and to point out ways to reduce mortality in the first month of life. The present study aims to describe methodological issues and to describe the sociodemographic profile of mothers whose newborns were considered near miss neonatal. A cross-sectional study was carried out in a case-control study at a Habitat Risk Maternity Unit in Aracaju, Sergipe, Brazil. Cases of NMN were identified and sociodemographic profile data were collected. Between March and September 2015, 6067 medical records were analyzed and 31 cases of NMN were identified, 1 being discarded due to collection error. Of the results found, part was of urban area, with an average age of 25.3 years, brown, less than 8 years of study and married or in stable union. In addition, 66.6% had some paid activity, had a monthly income of up to three minimum wages and just over half received some government aid, most of which were beneficiaries of the Bolsa Família Program.